A convenção nº 156 da OIT e a redução da jornada de trabalho de pais de crianças e adolescentes com necessidades especiais: as contribuições do Mercosul para o direito brasileiro - Webers, Aline Graziela Bald (Universidade do Vale do Rio dos Sinos, 2022)
To promote equality of opportunity and treatment of workers with family obligations and professional responsibilities, and, considering factors of discrimination in employment and the right to protection of children and youth, especially in the face of illness or serious limitation, the importance of ratification of Convention No. 156 of the International Labor Organization (ILO) by the MERCOSUR States Parties stands out. Bearing in mind that children or adolescents with special needs require specialized care from their guardians, who, as employees, are limited in providing it, the fundamental right of these children and adolescents is undermined, since there is limitation in the treatment of their condition, family life, special education, and formation. Considering that ILO Convention No. 156 aims to regulate equality of opportunity and treatment for workers in such family conditions, prioritizing better living and working conditions, the importance of the ratification of this instrument by Brazil is highlighted, in line with the other MERCOSUR State Parties. Furthermore, it should be noted that there is already a legislation in Brazil providing for the granting of special working hours to public servants who have a child or dependent with a disability. At the same time, based on the specific ILO’s Treaties and Conventions, on the constitutional principles of equality, human dignity, and protection, it’s intended to analyze the feasibility of ratifying this instrument, its impacts on MERCOSUR and ensuring the right to differentiated working hours to parents of children or adolescents with special needs in employment relations governed by the Consolidação das Leis do Trabalho (CLT) Consolidation of Labor Laws. In this context, the research problem is presented: How could the ratification of ILO Convention No. 156 and MERCOSUR contributions make it possible, in Brazil, to guarantee the reduction of working hours for parents of children and adolescents with special needs, without prejudice to remuneration and without discrimination in employment? As an initial hypothesis, Brazil could, in consonance with the other MERCOSUR States Parties, guarantee the reduction of working hours, without prejudice to remuneration or discrimination against parents of children with special needs, through the ratification of ILO Convention No. 156 and the adoption of the domestic law initiatives of the States Parties that apply the guidelines of this instrument, without prejudice to the observation of the recommendations of the SGT nº 10 towards the ratification and fulfillment of the ILO’s Conventions. The research will be divided into three stages: initially, the ILO and its Conventions will be studied, tracing the impact in integrated areas such as MERCOSUR. Next, an analysis of MERCOSUR will be carried out from the perspective of the labor law implemented by the bloc, in order to highlight existing human and social rights, exploring the SocioLabor Declarations and the Citizenship Statute. Finally, the possibility of ratification of ILO Convention nº 156 in Brazil will be investigated, as well as the feasibility of reducing the working hours of parents for the care and guarantee of the human/fundamental rights of children and adolescents with special needs, without employment discrimination. The research is qualitative, exploratory, carried out through the deductive, normative-descriptive, and comparative method, with bibliographic and documentary technical procedure.
Keywords: Convenção nº 156 da OIT; Direito Internacional do Trabalho; Direitos Humanos; Discriminação; Mercosul; ILO Convention nº. 156; International Labor Law; Human Rights; Discrimination; Mercosur; ACCNPQ::Ciências Sociais Aplicadas::Direito